Paciente masculino de 3 años con rinitis alérgica. - Franco Romero, Ginger Isabel (2021)
Allergic rhinitis is a chronic inflammatory disease mainly of the nasal mucosa distinguished by the presence of sneezing, nasal itching, nasal obstruction or congestion, and rhinorrhea. Approximately 10 to 20% of the Ecuadorian population suffers from allergic rhinitis. Thus showing a high incidence of this type of disease. In this work, the different types of rhinitis are specified, making further reference to allergic rhinitis, thus establishing its signs, symptoms, diagnosis and specific treatment.